Stromal Vascular Fraction: Biology and Application Outlook - V. N. Pavlov; A. A. Kazikhinurov; R. A. Kazikhinurov; M. A. Agaverdiev; I. F. Gareev; O. A. Beylerli; B. Z. Mazorov (Креативная хирургия и онкология, 2021)
Stromal vascular fraction (SVF) is a heterogeneous cell extract obtained with enzymatic dissociation of adipose tissue followed by centrifugation. This population includes many different cell types, i.a. adipose tissue stem cells (ATSCs), vascular endothelial and smooth muscle cells and their precursors, pericytes, fibroblasts, macrophages, T-lymphocytes, etc., excluding mature adipocytes. The main SVF component is ATSCs capable of self-renewal and multipotent differentiation. Since early research on SVF, an extensive effort has been aimed at understanding its clinical applications promoting a significant progress in the SVF use for treatment of various diseases and injuries. The past decade has witnessed an upward publication trend in basic and clinical research into the SVF therapeutic value. Manifold methods and devices for the SVF isolation from human liposuction lipoaspirate have been developed, continuously contributing to preclinical and clinical trials of its safety and efficacy. This review discusses the main properties and functions of the SVF cell population, its efficacy and safety for human therapy.